Pengaruh Implementasi Good Corporate Governance terhadap Kinerja Perusahaan Perbankan Umum Go Public pada Masa Krisis Ekonomi Global di Indonesia - Meilin Veronica; Tedy Setiawan Saputra (Universitas Indo Global Mandiri)
This research uses normality test, classic assumption test and multiple regression analysis method which aims to see the effect of the implementation of Good Corporate Governance (with indicators of the board of commissioners, audit committee and institutional ownership) on open public banking with indicators of Non Performance Loan (NPL), Loan to Deposit Ratio (LDR) and Capital Risk (CAR) during the global economic crisis in Indonesia. Research samples from publicly listed banking companies on the Indonesia Stock Exchange (IDX) and must have the research criteria. It is known that there are 45 banking companies that are active until the end of 2019 on the Indonesia Stock Exchange (IDX), but according to the research criteria there are only 25 banking companies with 2-year observation, year2018-2019, so the number of observation samples used is 50 samples. Based on the results of the research, it is realized that the implementation of Good Corporate Governance (GCG) has no effect on banking performance with financial performance measures, namely Non Performance Loans (NPL) and Loan to Deposit Ratio (LDR) in go public banks during the global economic crisis in Indonesia, but the results Hypothesis testing shows that the implementation of Good Corporate Governance (GCG) has a positive effect on the Capital Risk (CAR) variable in publicly traded commercial banks so that it is accepted because the implementation of Good Corporate Governance (GCG) will increase the supervision of the implementation of capital adequacy regulations set by the government.